The Way of the (Imagined) Sword: martial heritage perceptions among kendo practitioners (Revista de Artes Marciales Asiáticas, 2026)
Contemporary kendo (Japanese fencing) is a product of Imperial Japan and the post-WWII era. With its expansion to the West and democratic reformation, people from Europe and America engaged with its cultural heritage. However, there are few studies characterizing their kendo heritage notions. Hence, 30 semi-structed interviews were conducted to kendoka (kendo practitioners) residing in Spain asking them about aspects constituting “correct kendo”. By employing a Grounded Theory approach and open coding, four sub-categories emerged: ritual demarcation, material identity, traditional past, and kendistic identity. The main findings on these were that following protocol is fundamental to maintaining harmony and respect among practitioners; that the full uniform projected an idea of the samurai past as traditional, Japanese and value-charged; that ceremonies and ritual situate kendoka in a non-mundane context of the practice; that training implements invite to think of them as fitting for kendo and developing a “kendistic habitus”; and that kendo aesthetics and morals made it distinct from “mere sports”. Thus, both historical and mythical aspects of kendo are thought and reproduced by kendoka through intellectual and corporal means, then deriving in an embodied heritage that has to be interpreted by practitioners to manifest kendo's legacy.